2021
DOI: 10.3390/app11073047
|View full text |Cite
|
Sign up to set email alerts
|

Role B4C Addition on Microstructure, Mechanical, and Wear Characteristics of Al-20%Mg2Si Hybrid Metal Matrix Composite

Abstract: In the current study, the effect of different B4C additions (0, 2.5, 5, and 10 wt%) on the microstructural, solidification behavior, mechanical, and tribological properties of Al-20%Mg2Si composite were studied by means of scanning electron microscopy (SEM) equipped with energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), Vickers hardness, tensile, and dry sliding wear tests. The cooling curve thermal analysis (CCTA) approach was utilized to monitor the influence of B4C particles on the solidificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This phenomenon is consistent with previous research on the wear behavior of composites under sliding conditions, which has shown that wear rates increase with increasing load. [ 31 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is consistent with previous research on the wear behavior of composites under sliding conditions, which has shown that wear rates increase with increasing load. [ 31 ]…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is consistent with previous research on the wear behavior of composites under sliding conditions, which has shown that wear rates increase with increasing load. [31] The coefficient of friction between the wear pin and the counter disc as a function of the applied load is shown in Figure 5, and it was found that as the load increased, the coefficient of friction also increased. This is because an increase in the load results in an increase in the surface roughness, fracture, and damage of the pin contact surface, which leads to an increase in the frictional force acting on the pin.…”
Section: Cumulative Wear and Coefficient Of Friction Of Al-25mg 2 Si ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The improved wear resistance was attributed to B 4 C's self-lubrication feature. 42 In the event of greater speeds, a significant amount of plastic deformation, as well as deeper grooves were observed. 43…”
Section: Effect Of Load Variation On Wear Propertiesmentioning
confidence: 98%
“…Al MMCs are generally produced with pure aluminum or aluminum alloys as their matrix materials. Due to their unique properties, such as a light weight, high specific strength, reasonable wear and corrosion resistance, controlled coefficient of thermal expansion, and high, good elevated-temperature stability, they are widely used in automobile and aerospace industries in the design of parts for advanced applications [11,12]. The density of aluminum alloys is nearly the same as the density of pure aluminum, which is approximately 2698 kg/m 3 .…”
Section: Introductionmentioning
confidence: 99%